Comparison of Middle Latency Auditory Evoked Potential Results of Congenitally Blind, Partial Vision Deficiency to Normal Vision Aquity Subjects - (:unkn) unknown (AVES, 2010)
Objective: The auditory abilities of congenitally blind, partial vision deficiency and normal vision groups were tested using middle latency response test which is an auditory evoked potential test reflecting the primary and secondary auditory area activities. The objective of the Auditory Middle Latency Response Test was to find out differences in wave latency and amplitude among the groups. Materials and Methods: Eleven congenitally blind people composed the first group, the second group included 10 subjects with partial vision deficiency. Thirteen subjects with normal vision were in the third group. The age range of the subjects were between 18-30 years. All the participants had normal hearing. Auditory Middle Latency Response (AMLR) test was applied to all subjects and AMLR results were recorded from Fz and Cz electrode localizations. Results: In the Cz recordings, there was a significant difference between Pa and Nb wave latency values among the groups. Average Pa wave latency of the first group was longer than that of the third group. Average Nb wave latency of the first group was longer than Nb wave latency of the second group. In the Fz recordings, average Pb wave latency of the first group was significantly longer than that of the second group and third group. In Cz and Fz recordings, there were no significant differences between Po-Na, Na-Pa, Pa-Nb, Nb-Pb amplitudes among the groups. Conclusion: Results of Cz and Fz recordings indicated longer Pa and Nb wave latency in the congenitally blind group than in the other groups. No significant amplitude difference was present among the groups.